HEART RATE VARIABILITY INDICES IN PATIENTS WITH VIRAL HEPATITIS - Lavelin, S.B.; Panchuk, S.N.; Gololobova, O.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The results of research of time and spectral domens of heart rate variability (HRV) changes in 26 patients with viral hepatitis (VG) in the state of relative rest and with the orthostatic test are presented. It is shown that the HRV parameters in clinostasis have minor correlation with the clinical or biochemical parameters of VG. The HRV indeces in orthostatic test have middle and high positive correlation with the levels of direct and indirect bilirubin of blood serum. Our results showed the necessity of the purposeful study HRV at VG.